Dome of eden : a new solution to the problem of creation and evolution - Webb, Stephen H., 1961- (Eugene, Or. : Wipf and Stock Publishers, 2010)
This book does not try to harmonize evolution and creation. Harmonizers typically begin with Darwinism and then try to add just enough religion to make evolution more palatable, or they begin with Genesis and pry open the creation account just wide enough to let in a little bit of evolution. By contrast, Stephen Webb provides a theory of how evolution and theology fit together, and he argues that this kind of theory is required by the internal demands of both theology and biology. The Dome of Eden also develops a theological account of evolution that is distinct from the intelligent design movement. Webb shows how intelligent design properly discerns the inescapable dimension of purpose in nature but, like Darwinism itself, fails to make sense of the problem of natural evil. Finally, this book draws on the work of Karl Barth to advance a new reading of the Genesis narrative and the theology of Duns Scotus to provide the necessary metaphysical foundation for evolutionary thought - Publisher info.
The theory that would not die -- Re-trying scopes: what Machen would have done to Darrow -- Three rival theories and the problem of natural evil -- The five theses -- Karl Barth on the edge of the gap -- The dome of domes divides the world -- Could Jesus have been an octopus? (Dunes Scotus replies to Darwin) -- An ethics of pets vs. the Darwinian sublime -- The nature of naturalism.
Includes bibliographical references and an index.
Print version record.
Keywords: Bible and evolution; Evolution -- Religious aspects -- Christianity; Good and evil; Theodicy; Bible and evolution; Evolution -- Religious aspects -- Christianity; Good and evil; Theodicy; RELIGION / Christian Theology / General; Electronic books